Gender Perspective as Formality: Feminist Policy Analysis toward RPJMN 2015-2019 and Strategic Plan of KPPPA 2015-2019 - Anita Dhewy (Jurnal Perempuan, 2017)
Although RPJMN 2015-2019 states that gender mainstreaming becomes a policy direction, but actually gender perspective has not become an integral part. In fact, in some parts, policies of RPJMN 2015-2019 are still gender neutral. The author uses the framework of feminist policy analysis to uncover the limitations of RPJMN 2015-2019 and KPPPA 2015-2019 in using, translating and implementing gender perspective. Feminist analysis also found that sexual and reproductive health and rights (SRHR) has not been recognized in RPJMN 2015- 2019 and renstra KPPPA 2015-2019. Moreover, there is a potential of elimination of women issue and other marginalized groups from development agenda due to development policies that tend to lead to new developmentalism model.